A Versatile Method to Create Antibody/Split‐Enzyme Complexes and Its Application to a Rapid, Homogeneous, and Universal Electrochemical Immunosensing System - Yuka Tobita; Kensuke Hirano; Daimei Miura; Yuma Hatano; Wakako Tsugawa; Kazunori Ikebukuro; Koji Sode; Ryutaro Asano (Advanced Sensor Research)
Abstract In this study, a versatile method is developed to create an antibody/split‐enzyme complex for use in electrochemical immunosensors. SpyCatchers are genetically fused at each terminus of flavin adenine dinucleotide‐dependent glucose dehydrogenase (FAD‐GDH) and a protease recognition sequence is inserted into a loop region to prepare a soluble protein and the split GDH. SpyTag‐fused single‐chain variable fragments (scFvs) are employed, which leads to the simple preparation of antibody‐split enzyme complexes (split AECs). The addition of pentameric C‐reactive protein (CRP), as a representative multimeric protein, restored the GDH activity of the split AECs, as the two split AEC fragments formed active GDH when in close proximity. CRP in human serum is electrochemically detected within 5 min without any washing steps with a clinically relevant CRP detection range (0.03–1 mg dL−1). The detection system is expanded to detect hemoglobin, SARS‐CoV‐2 spike protein, and inactivated SARS‐CoV‐2 by exchanging the scFvs. These results show that the convenient preparation method of the split GDH and the split AEC by the insertion of the protease recognition sequence and the use of SpyCatcher/SpyTag can realize a rapid, homogeneous, and universal electrochemical detection system that can be integrated into a commercially available electrochemical glucose sensor.